Search All of the Math Forum:
Views expressed in these public forums are not endorsed by
NCTM or The Math Forum.


Elana
Posts:
22
Registered:
12/6/04


More algebraic proofs
Posted:
Apr 23, 2005 1:28 PM


Hello, all! I have to prove the following: if a + b + c = 0, then (a^2 + b^2 + c^2)^2 = 2(a^4 + b^4 + c^4).
Here is what I have so far:
I worked out the square for the left side, and got a^4 + b^4 + c^4 + 2(a^2b^2 + a^2c^2 + b^2c^2). Taking out the ^4 terms, I now have a new equality to prove:
2(a^2b^2 + a^2c^2 + b^2c^2) = a^4 + b^4 + c^4
I tried several approaches, without success. I tried to rewrite that as (a^2 + b^2)^2 +c^4 = 4(a^2b^2 + a^2c^2 + b^2c^2). Didn't get anywhere. Also tried 2a^2b^2 + a^4 + b^4 = c^4 + 2a^2c^2 + 2b^2c^2, getting (a^2 + b^2)^2 + 2a^2b^2 = c^3 ( c 1 ). Stuck again.
Please, set me on the right track.
Elana



